Effects of the anxiolytic benzodiazepine oxazepam on freshwater gastropod reproduction a prospective study - Lebreton, Morgane (Ecotoxicology (London, England), 2021)
© 2021. The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature.